2020
DOI: 10.1016/j.molcel.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage-Induced Nucleosome Depletion Enhances Homology Search Independently of Local Break Movement

Abstract: Highlights d Intrinsic and break-induced chromatin dynamics show cellcycle dependence d Uls1 STUbL regulates local DSB dynamics through MRX and cohesin turnover d Chromatin expansion and ectopic movement are critical for DSB repair by HR d Loss of centromere tethering is not a major DNA damage response

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 80 publications
8
67
0
Order By: Relevance
“…Benefiting from the ability of iPOC to investigate the overall histone composition in chromatin, we observed that while in the chromatin input the abundance of most histones declined upon IR, this effect was generally less pronounced for DNA-bound histones identified through iPOC (Fig.S5K). Our data are therefore in line with the recently reported proteasome-mediated depletion of histones (Cheblal et al, 2020), but suggest that soluble histones might strongly contribute to this phenomenon. Even more interestingly, in iPOC we observed that changes in DNA-bound histones during DSB repair occurred in a time- and histone variant-specific manner, sometimes even leading to a transient increase (e.g.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Benefiting from the ability of iPOC to investigate the overall histone composition in chromatin, we observed that while in the chromatin input the abundance of most histones declined upon IR, this effect was generally less pronounced for DNA-bound histones identified through iPOC (Fig.S5K). Our data are therefore in line with the recently reported proteasome-mediated depletion of histones (Cheblal et al, 2020), but suggest that soluble histones might strongly contribute to this phenomenon. Even more interestingly, in iPOC we observed that changes in DNA-bound histones during DSB repair occurred in a time- and histone variant-specific manner, sometimes even leading to a transient increase (e.g.…”
Section: Resultssupporting
confidence: 93%
“…Our results indicate that upon DNA damage BRG1 is recruited at DSB sites to promote a specific chromatin state that facilitates HR; in addition, we determined a direct role for TRA2b during HR, beyond its canonical function in RNA splicing (Tacke et al, 1998). Moreover, our observations clarify the controversial role of HMGA2 in DDR (Palmieri et al, 2011) and indicate that, similar to 53BP1, this transcriptional regulator is recruited at MDC1 sites upon DSB induction and negatively regulates HR, thus playing a major role in NHEJ as recently reported for HMGB1 (Cheblal et al, 2020).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…4C , top panel; Supplementary Video 6 ). Experimental support for targeted-loading of LEFs at DSB ends come from recent studies that observed accumulation of SMC1 at DSBs sites leading to a ∼2-10-fold cohesin enrichment at restriction-enzyme induced DSB sites [45, 52] though two other studies reported cohesin enrichment only for S/G2 cells but not G1 cells via laser induction [53, 54], suggesting that further experimental work is needed. To test how targeted loading of LEFs to DSB ends aids synapsis, we implemented simulations where loading of LEFs within 1 kb of the DSB is 250-, 500-, 750-, 1000-, 5000- or 10000-fold more likely than at other similarly-sized genomic loci; this corresponded to about 5%, 9%, 13%, 17%, 50% or 67% of LEF loading events occurring at the DSB sites in our simulations.…”
Section: Resultsmentioning
confidence: 99%
“…Third, long-lived LEFs may correspond to acetylated STAG1-cohesins [49], or LEFs of a different kind that exhibits higher processivity. Fourth, we suggest that targeted LEF loading at DSBs may be mediated by the MRX complex as knockdown of MRX led to a significant decrease in cohesin loaded at DSBs [52]. Fifth, we speculate that LEF stabilization by DSBs may be mediated by the ATM complex, which phosphorylates cohesins and accumulates cohesins in the DSB-containing TAD [45].…”
Section: Discussionmentioning
confidence: 99%